Revisiting the Karyotypes of Alligators and Caimans (Crocodylia, Alligatoridae) after a Half-Century Delay: Bridging the Gap in the Chromosomal Evolution of Reptiles - Oliveira, Vanessa C S; Altmanová, Marie; Viana, Patrik F; Ezaz, Tariq; Bertollo, Luiz A C; Ráb, Petr; Liehr, Thomas; Al-Rikabi, Ahmed; Feldberg, Eliana; Hatanaka, Terumi; Scholz, Sebastian; Meurer, Alexander; et al. (Cells, 2021)
Although crocodilians have attracted enormous attention in other research fields, from the cytogenetic point of view, this group remains understudied. Here, we analyzed the karyotypes of eight species formally described from the Alligatoridae family using differential staining, fluorescence in situ hybridization with rDNA and repetitive motifs as a probe, whole chromosome painting (WCP), and comparative genome hybridization. All Caimaninae species have a diploid chromosome number (2n) 42 and karyotypes dominated by acrocentric chromosomes, in contrast to both species of Alligatorinae, which have 2n = 32 and karyotypes that are predominantly metacentric, suggesting fusion/fission rearrangements. Our WCP results supported this scenario by revealing the homeology of the largest metacentric pair present in both Alligator spp. with two smaller pairs of acrocentrics in Caimaninae species. The clusters of 18S rDNA were found on one chromosome pair in all species, except for Paleosuchus spp., which possessed three chromosome pairs bearing these sites. Similarly, comparative genomic hybridization demonstrated an advanced stage of sequence divergence among the caiman genomes, with Paleosuchus standing out as the most divergent. Thus, although Alligatoridae exhibited rather low species diversity and some level of karyotype stasis, their genomic content indicates that they are not as conserved as previously thought. These new data deepen the discussion of cytotaxonomy in this family.
Keywords: Karyotype; molekulární evoluce; Chromosomes; karyotyp; Evolution, Molecular; chromozomy; zvířata; Comparative Genomic Hybridization; Alligators and Crocodiles; Animals; srovnávací genomová hybridizace; In Situ Hybridization, Fluorescence; aligátoři a krokodýli; hybridizace in situ fluorescenční